Instagram post: Writing caption through process approach in developing writing skill - Mauliya Avivi; Fika Megawati (EduLite: Journal of English Education, Literature and Culture, 2020)
Instagram has some features for supporting English learning process. Posting a picture and adding a caption could be a way for developing writing skill. Instagram users are allowed to write caption through process approach that would guide them to make a good writing. This study aims to find out the effect of Instagram caption through process approach on students’ writing skill in recount text. Quasi-experimental design was implemented to the two classes of Multimedia students at one of Indonesian vocational high schools. Each class participated in this study consisted of thirty students. The data collection was taken from tests, pre-test and post-test. Then, it was analyzed using Independent t-test. The result of this study indicates that Instagram caption through process approach gives positive effect for developing English writing skill. More specifically, the students are able to use their Instagram account as an alternative way to learn English by sharing their experience, strengthen their step in writing skill through editing and revising the draft based on the teacher’s feedback, and publish writing product. This study implies that feature in Instagram gives advantages for English teachers and students, and it can be promoted as an attractive educational technology for writing activities.